The Construction of a Skin-on-Frame Canoe at Kierikki Stone Age Centre, Finland, as a Medium for Group Training in Ancient Skills and Experiential Learning - Peter Groom; Patrick Sweeney; James Findlay (EXARC Journal)
In July 2018 a group of students from the UK participating in the Placements in Environmental, Archaeological and Traditional Skills (PEATS) Erasmus + Work Placement, attended the Kierikki Stone Age Centre, Pahkalantie, Finland. Part of that training included experimental / experiential projects that were coordinated by Dr. Peter Groom of the Mesolithic Resource Group. Next to the authors also involved in the construction of a skin-on-frame canoe were: Alice Angeline, Jonathan Cusdin, Emily Elsmore, Evon Kirby, India McDermott, Katie Rose Prideaux, Lottie Rogers, Jasmine Savill.